The Effect of Spent Fluid Catalytic Cracking Filler on Performance Testing of Asphalt Concrete Mixture - Anh Thang Le; Manh Tuan Nguyen; Van Phuc Le (Advances in Materials Science and Engineering)
The spent fluid catalytic cracking (SFCC), waste from the petroleum industry, is nonstop increasing and causing environmental pollution in Vietnam. This study is an attempt to recycle SFCC in pavement construction. The study investigated the effect of SFCC, as a filler material in the hot-mix asphalt (HMA), on the essential characteristics of the asphalt concrete mix. First, the optimum percentages of bitumen and SFCC rate were investigated based on the Marshall design method. The HMA with SFCC showed more enhanced stability, flow, and other Marshall properties than the asphalt concrete mixture with the optimum limestone filler of 5%. Besides, the effects of SFCC rates on Marshall characteristics were explored. Second, performance tests were conducted to compare the mix with the different optimum content fillers of SFCC, limestone, and Portland cement. The tests include wheel tracking, indirect tensile, fatigue, and dynamic modulus tests to evaluate the performance of HMA with SFCC. It was found that the asphalt mixture with the optimum SFCC filler content can enhance pavement performance and improve the rutting and cracking resistance of the asphalt pavement.